Role of Women Entrepreneurs in Social and Economic Development in India: Exploring the Impact of Women Entrepreneurs on India's Economic and Social Development (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Women entrepreneurs have a critical impact in addition to business enterprise, they affects financial development even business creation and financial growth these are viewed as a way to produce work opportunity. The status of woman in India has been changing because of developing industrialization, globalization, and social enactment. With the view of training and social status, woman has moved from kitchen to larger amount of expert exercises. Business growth among woman is significant for the accomplishment of more extensive growth objectives, for example, development with value. Studies demonstrate that numerous woman business people are discovered working in troublesome circumstances when contrasted with their male partners.